(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
During the years of independence, attention to the sports and cultural sphere has increased in all regions of Uzbekistan. Important reforms in this area have also been carried out in the Mirishkor district of the Kashkadarya region. This article presents the potential of the district in the sports and cultural sphere, the results achieved, and the specific aspects of the cultural life of the district.